Modified design procedures for bridge pile foundations subjected to liquefaction-induced lateral spreading. Issue 2 (6th April 2017) - Khosravifar, Arash; Nasr, Jonathan
Abstract : Effective-stress nonlinear dynamic analyses (NDA) were performed for piles in the liquefiable sloped ground to assess how inertia and liquefaction-induced lateral spreading combine in long- and short-duration motions. A parametric study was performed using input motions from subduction and crustal earthquakes covering a wide range of durations and amplitudes. The NDA results showed that the pile demands increased due to (a) longer duration shakings, and (b) liquefaction-induced lateral spreading compared to nonliquefied conditions. The NDA results were used to evaluate the accuracy of the equivalent static analysis (ESA) recommended by Caltrans/ODOT for estimating pile demands. Finally, the NDA results were used to develop new ESA methods to combine inertial and lateral spreading loads for estimating elastic and inelastic pile demands.